The impact of the industrial policy on regional development in Ukraine - Nosova, Olga (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2017)
The paper deals with the study of the role of industrial policy on regional development, and aims to formulate the basic measures for future structural adjustments in Ukraine. Theoretical analysis of various approaches confirms market imperfection and proves the necessity of further empirical research in the field of assessment of the effectiveness of industrial policy. The use of a complex approach, bounded rationality and socio-economic dynamics provides a transdisciplinary view on a broad range of industrial policy considerations. The progress in reforming process in the regions depends on the success of industrial policy providing different measures of support (including protection and production subsidies) across industries to see whether supported industries exhibit faster growth. Studies on economic growth and trade policies confirm the existence of a strong correlation between growth rate of trade and regions’ economic performance. The analysis of two groups of factors – general and specific sources of the growth of transition economy – is directed on estimation of the effects of regional industrial policy in Ukraine. The first group of indices includes industrial output, fixed capital accumulation, human capital accumulation, economically active population, growth of R&D expenditures, macroeconomic stability, monetary indices, foreign trade, and foreign direct investments. The aggregate transition specific factors combine the indicators of success of reforms, including labour productivity, capital intensity, technological change, regional differences. The regional imbalance assessment is determined by the gross regional product per capita, regional employment, and expenditures on education.